Lentil and Mungbean protein isolates: Processing, functional properties, and potential food applications. (February 2023) - Shrestha, Smriti; van 't Hag, Leonie; Haritos, Victoria S.; Dhital, Sushil
Abstract: Among the wide range of plant-based protein sources, pulse proteins stand out for their nutritional values and functional properties, together with sustainability. The global attention on soy and pea proteins, however, has overlooked other pulses. This review has explored underutilized and under-researched pulses, lentils and mungbean, by considering their comparable protein contents but different protein composition to that of soy and pea proteins. The traditional subsistence farming of lentils and mungbean has evolved with their emergence in the global agriculture sector. Research on lentil and mungbean protein extraction, however, has not been as extensive as for soy and pea. The novel dry fractionation methods benefiting protein native structure are in the early stage of optimizing protein yield. The milder wet extraction techniques-ultrafiltration or salt extraction-dilutive precipitations-have been investigated to a lesser extent. The harsh conventional wet extraction, i.e. alkaline extraction-isoelectric precipitation, is widely employed for lentils and mungbean. Apart from extraction method, drying process, pH condition, and genetic makeup of the plants directly influence protein functional properties. Protein functional properties, including gelation, emulsification, water holding (WHC) and oil absorption capacities (OAC), and foaming of lentils and mungbean, are discussed to understand their potentiality in the development of meat analogs. Lentil protein exhibited comparable gelling, emulsifying, and superior foaming properties to pea and soy protein. Meanwhile, the gelling, WHC and OAC of mungbean proteins are comparable to soy. This review highlights the promising application of lentil and mungbean proteins as sustainable plant-based protein sources for human food applications. Graphical abstract: Image 1 Highlights: Globulin protein composition is different between lentils and mungbeans. Lentil protein exhibited comparable functional properties to pea and soy protein. Gelling, water holding and oil absorption of mungbean proteins are comparable to soy. Lentil and mungbean protein isolates are best suited for emulsion-type meat analogs. Lentils and mungbean has promising application as sustainable plant-based protein sources.